A historical study of John Graham Lake and South African/United States pentecostalism - Burpeau, Kemp Pendleton (Rhodes University, Faculty of Humanities, Department of History, 2002)
American minister John Graham Lake (1870-1935) was a pivotal participant in an era of profound religious and political transition. Surprisingly, Lake's often provocative life had previously been largely neglected as a field of academic inquiry. In the U.S. Lake associated with key Holiness, Wesleyan and Apostolic Faith charismatics like John Alexander Dowie of the Zion City, Illinois Utopia, Charles Parham of the Topeka Revival and William Seymour of the Azusa Street Revival. Lake served as an important intermediary between Parham's often reactionary, white orientation that was unreceptive to an enthusiastic black liturgy and Seymour's expansive African-American egalitarianism expressed through exuberant spirit manifestations. Lake's South African ministry was shaped by his middle class white business background, Azusa Street message and American perspectives. He brought together the faith healing movement inspired by Dutch Reformed minister Andrew Murray, P. Ie Roux's black and white Zion charismatic adherents affiliated with Dowie and the new U.S. Pentecostalism of Parham and Seymour. Lake's African-American influenced Pentecostalism was compatible with indigenous African worship. His emphasis on the spiritual needs of the disempowered found a receptive audience in talented black evangelists Elias Letwaba and Edward Lion. Even though acquainted with Mohandas Gandhi, Lake did not undertake a South African social gospel-type civil protest against societal injustice. In fact, Lake's participation with Afrikaner politicians like Louis Botha in fashioning a segregationist land use law was most troubling. Lake was ambivalent about racial integration. His belief in an egalitarian status for all Christians, his Populist/Progressive ethics and his enthusiastic promotion of women's rights were complicated by his advocacy, or at least tolerance, of some disparate racial treatment in his Apostolic Faith Mission and South African society at large. Lake's paternalism and notion of Westem cultural superiority conflicted with his love of all persons. Lake's otherworldly prioritization of individual spiritualism over a socioeconomic agenda usually stymied activism. His uncharacteristic use of nonviolent protest to protect faith healing formed a remarkable contrast with his reluctance to actively campaign against unequal racial treatment in Africa and America. Historiographical perspectives on Lake range from the saintly pioneer charismatic missionary to the Elmer Gantry type charlatan acting only for personal benefit. Lake was a unique personality with his flamboyant rhetoric, strong convictions and feelings of personal worth. His distinctive Jesus as healing and suffering God theology evidenced both consistency with precedent as well as creative anticipation. Shortcomings resulting from his preference to address social concerns on an individual spiritual rather than societal level, his liberties with truth and his bad business judgments resulting in litigation. Nevertheless, Lake's life demonstrated that a gifted but imperfect instrument could accomplish a meaningful ministry.,Adobe Acrobat Pro 9.5.4,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Lake, John G; Pentecostalism -- South Africa; Pentecostalism -- United States; Pentecostals; Christianity and politics -- South Africa